Hydrodeoxygenation of Sorbitol into Bio‐Alkanes and ‐Alcohols Over Phosphated Ruthenium Molybdenum Catalysts. Issue 21 (18th October 2018) - Weng, Yujing; Wang, Tiejun; Wang, Chenguang; Liu, Qiying; Zhang, Yulong; Duan, Peigao; Wang, Longlong; Yin, Hongxing; Liu, Shijun; Ma, Longlong
Abstract: Biofuels such as renewable alkanes and higher alcohols have drawn considerable interests for the use in internal combustion engines. Especially, higher alcohols could be used as a blending agent for diesel fuels. Herein, carbon supported phosphated ruthenium‐molybdenum (RuMoP) catalysts were employed in continuous trickle‐bed reactor for converting sorbitol into renewable alkanes and higher alcohols. The results showed that RuMoP on an active carbon (AC) support presented a complete sorbitol conversion and high yields of alkanes and alcohols in gasoline and diesel range. Subsequently, carbon nanotube (CNT) supported RuMoP was prepared and studied in detail for comparison. RuMoP/CNT presented a low C−C bond cracking property in sorbitol conversion and high selectivity of C6 products in gas‐phase (C6 alkane, 74.7 %) and oil‐phase (C6 alkane and alcohols, 87.8 %). Finally, detailed characterizations (N2 ‐adsorption, XRD, HRTEM, XPS, NH3 ‐TPD, Py‐IR spectrums, etc.) were performed over relevant catalysts (RuMoP/C and RuMoP/CNT) for correlating their catalytic and physicochemical properties. Abstract : Get a move on ! Biofuels such as renewable alkanes and higher alcohols have drawn considerable interests. Herein, carbon supported phosphated ruthenium‐molybdenum (RuMoP) catalysts were employed in continuous trickle‐bed reactor for converting sorbitol into renewable alkanes and higher alcohols. The results showed that RuMoP catalysts presented a complete sorbitol conversion and high yields of alkanes and alcohols in gasoline and diesel range. Finally, detailed characterizations were performed over relevant catalysts for correlating their catalytic and physicochemical properties.